2015
DOI: 10.1111/labr.12047
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Effects of Public‐Sector Unions

Abstract: www.econstor.eu Macroeconomic effects of public-sector unionsAleksandar Vasilev * January 6, 2015 AbstractMotivated by the highly-unionized public sectors, the high public shares in total employment, and the public-sector wage premia observed in Europe, this paper examines the importance of public-sector unions for macroeconomic theory. The model generates cyclical behavior in hours and wages that is consistent with data behavior in an economy with highly-unionized public sector, namely Germany during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In Vasilev (), a standard RBC was parameterized for Germany, which showed that without the rigidity the fit is much worse.…”
mentioning
confidence: 99%
“…In Vasilev (), a standard RBC was parameterized for Germany, which showed that without the rigidity the fit is much worse.…”
mentioning
confidence: 99%
“…In the next subsection, as in Vasilev (2015), we investigate the dynamic correlation between labour market variables at different leads and lags, thus evaluating how well the model matches the phase dynamics among variables. In addition, the autocorrelation functions (ACFs) of empirical data, obtained from an unrestricted VAR(1), are put under scrutiny and compared and contrasted to the simulated counterparts generated from the model.…”
Section: Out Of Steady-state Model Dynamicsmentioning
confidence: 99%
“…Such a mark-up is a stylized fact for the major EU economies, e.g. Vasilev (2015b). The production function of public services is as follows: , 0, 0, ( 0, ( ) )…”
Section: Governmentmentioning
confidence: 99%